Neonatal management of parvovirus B19-induced hydrops fetalis: a case report - Colombo, Marco; Lorioli, Laura; Pagani, Riccardo; Patanè, Luisa; Cheli, Maurizio; Mangili, Giovanna (Frontiers in Pediatrics, 2025)
BackgroundHydrops fetalis (HF) is a severe fetal condition, and congenital Parvovirus B19 (B19V) infection is a leading cause of the non-immune form (NIHF). The recent European B19V outbreak has had a substantial impact on obstetric and neonatal outcomes, leading to an increase in fetal anemia, NIHF, spontaneous abortions, and intrauterine demise. While prenatal diagnosis and intrauterine interventions are well established, postnatal management of B19V-related NIHF remains challenging and outcomes are often poor.Case presentationWe report a preterm newborn with B19V-associated NIHF following intrauterine transfusions for severe fetal anemia. At birth, the neonate had generalized edema, ascites, and respiratory compromise. Despite aggressive medical management, the patient developed persistent, refractory edema.InterventionGiven the failure of conservative therapy, peritoneal dialysis (PD) was initiated as a rescue strategy. PD allowed gradual interstitial fluid removal, microcirculatory recovery, and functional “renal rest” after prolonged pharmacologic stress.OutcomeThe neonate progressively improved, with resolution of edema, normalization of renal function, and successful respiratory weaning. At 12 months of corrected age (CA), neurodevelopmental milestones were appropriate, although ongoing long-term surveillance is warranted.ConclusionThis case contributes to the limited evidence on postnatal management of B19V-related NIHF. PD may be considered in neonates with persistent, refractory edema despite maximal conventional therapy, with careful individualization of treatment. Further research, including multicenter registries and controlled studies, is needed to define its role within standardized neonatal care protocols.